Supervisory Monitoring Technology System for Key Drinking Water Sources in Guangdong-Hong Kong-Macao Greater Bay Area - CUI Fan; KOU Xinyue; FENG Youbin; XIE Yuning; HE Yingqing; ZHENG Ning (Renmin Zhujiang)
In order to resolve the contradiction between the high demand for water resources,water ecology and water environment in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) and the insufficient supervision capabilities in the water conservancy industry,and achieve the transformation from passive management to active management of key drinking water sources in the GBA,this paper carries out supervisory monitoring of key drinking water sources through remote sensing macro monitoring,UAV cruise monitoring,fixed-point monitoring and other intelligent monitoring technology system.The results show that:①After application of a supervisory monitoring technology system for key drinking water sources,the full-coverage,dynamic and quasi-real-time monitoring of 35 key water sources in the GBA is realized,and the risk sources and water problems can be identified efficiently.②For identifying five suspected risk sources in water source areas,namely construction projects,key river (reservoir) tributaries,temporary shipping stops,material stacking places,agricultural production activities by remote sensing macro monitoring and UAV cruise monitoring,the accuracy rate is 65.7%.③For the chlorophyll a and CODMn monitoring of the water source of main Guangzhou-Dongguan-Huizhou Dongjiangbei River by remote sensing macro monitoring and artificial fixed-point monitoring during the same period,the monitoring results of the two technical means are in good agreement.Therefore,with application of the technology system in supervision and management of key drinking water sources,the smart water conservancy supervision and business management are deeply integrated,and the effective technical means for supervision and management are available.